Presence and prognostic value of ventricular diastolic function in arrhythmogenic right ventricular cardiomyopathy. Issue 11 (27th May 2020) - Sadeghpour, Anita; Hosseini, Leila; Rezaeian, Nahid; Alizadehasl, Azin; Maleki, Majid; Emkanjoo, Zahra; Bakhshandeh, Hooman; Zadehbagheri, Fatemeh
Abstract: Introduction: Limited data exist regarding the presence and importance of diastolic parameters in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC). We sought to evaluate RV diastolic parameters and echo‐based diastolic predictors of major adverse cardiovascular events (MACE). Method: 48 patients with a definitive diagnosis of ARVC were included and followed for 6‐18 months. A comprehensive standard two‐dimensional (2D) transthoracic echocardiography (TTE) with precise evaluation of systolic and diastolic indices of both ventricles was done. RV isovolumetric relaxation time (IVRT), RV myocardial performance index (MPI), and right atrial (RA) volume were evaluated. Results: 48 patients (mean age = 38.5 ± 14 years; 79.2% male) were enrolled. 27.3% had grade I, 68.2% had grade II, and 4.5% had grade III RV diastolic dysfunction. In 12‐month follow‐up, 12 patients (25%, with mean RV3DEF = 24.8 ± 9%) experienced MACE and required hospitalization: ventricular tachyarrhythmia in 7 patients (14.6%), RV clot in 2 subjects (4.2%), and right‐sided failure in 3 cases (6.3%). In logistic regression analysis, tissue Doppler velocity of tricuspid annulus (e' TV) ( P  = .02, OR = 0.581, CI = 0.368‐0.917), peak E mitral valve ( P  = .043, OR = 0.95, CI = 0.913‐0.999), tissue Doppler velocity of septal e' ( P  = .052, OR = 0.733, CI = 0.536‐1.003), and MPI ( P  = .009, OR = 95, CI = 3.083‐2942) were powerful predictors of MACE. Conclusion: In our study, RV diastolic function parameters including e' TV and e′ MV, RA volume and area, and RV MPI were powerful predictors of MACE and may be considered during the baseline and follow‐up of the ARVC patients.